1994
DOI: 10.1083/jcb.127.4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Making a connection: direct binding between keratin intermediate filaments and desmosomal proteins.

Abstract: Abstract. In epidermal cells, keratin intermediate filaments connect with desmosomes to form extensive cadherin-mediated cytoskeletal architectures. Desmoplakin (DPI), a desmosomal component lacking a transmembrane domain, has been implicated in this interaction, although most studies have been conducted with cells that contain few or no desmosomes, and efforts to demonstrate direct interactions between desmoplaldn and intermediate filaments have not been successful. In this report, we explore the biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
207
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(226 citation statements)
references
References 43 publications
13
207
3
Order By: Relevance
“…Indeed, loss of desmosomal proteins has been shown to increase epithelial cell migration (Rieger-Christ et al, 2005;South et al, 2003). CKs connect with desmosomes to form extensive cadherin-mediated cytoskeletal structures (Buhler & Schaller, 2005;Kouklis et al, 1994;Smith & Fuchs, 1998). These data would therefore be consistent with the idea that the loss of CK expression can promote an invasive phenotype through a mechanism that elevates migratory ability by down-regulating desmosomal proteins.…”
Section: Epithelial-mesenchymal Transition (Emt) and Cytokeratinssupporting
confidence: 77%
“…Indeed, loss of desmosomal proteins has been shown to increase epithelial cell migration (Rieger-Christ et al, 2005;South et al, 2003). CKs connect with desmosomes to form extensive cadherin-mediated cytoskeletal structures (Buhler & Schaller, 2005;Kouklis et al, 1994;Smith & Fuchs, 1998). These data would therefore be consistent with the idea that the loss of CK expression can promote an invasive phenotype through a mechanism that elevates migratory ability by down-regulating desmosomal proteins.…”
Section: Epithelial-mesenchymal Transition (Emt) and Cytokeratinssupporting
confidence: 77%
“…Keratin 5 is an intermediate filament (IF) protein that binds specifically to desmoplakin in keratinocytes (32). Immunoprecipitation of keratin 5 on IMOK cells in the presence or absence of a desmoplakin siRNA revealed that immunoprecipitated keratin 5 bound much less to iASPP in the presence of a desmoplakin siRNA compared with scrambled siRNA control (Fig.…”
Section: Loss Of Iaspp Increases Desmoplakin Phosphorylation and Solumentioning
confidence: 99%
“…E-mail address: t.magin@uni-bonn. and yeast 2 hybrid assays demonstrated that the amino terminal head domain of type II keratins (e.g., K5) binds to the C-terminal tail of desmoplakin I, whereas no association was seen with type I keratins (Kouklis et al, 1994;Meng et al, 1997). More recently, it was shown that the major hemidesmosomal plaque protein plectin interacts with K14 but not with K5 (Geerts et al, 1999).…”
Section: Introductionmentioning
confidence: 99%